A study of evaluation of various risk factors of retinal vein occlusion - Prajapati, Vaishali Amrutlal; Vasavada, Dhaivat; Patel, Shashank M.; Chauhan, Wilhemina; Prajapati, Vipul (International Journal of Research in Medical Sciences, 2017)
Background:A study of various ocular & systemic risk factors in Retinal Vein Occulation (RVO) at tertiary eye care centre. Methods:A prospective study included 50 eyes of 50 patients, in period of September 2010 to August 2012. Inclusion criteria: 1. Age >25 years, 2. All newly diagnosed cases of vein occlusion. Exclusion criteria: 1. Age <25 years 2. All other ocular diseases causing significant visual impairment. A detailed history, ophthalmic & systemic examinations with all necessary investigations-as and when required were done. Results: In our study, RVOs were more common in males – 26 (52%) & in 56-65 years of age group - 16 (32%). BRVO (Branch Retinal Vein Occlusion)s were more common than CRVO (Central Retinal Vein Occlusion) - Nonischemic (26%) >Ischemic (24%). In risk factors - most common was hypertension - in 38 (76%) patients. Followed by descending order, hyperlipidemia 27 (54%) >diabetes mellitus 16 (32%) >tobacco 14 (28%) >hyper homocystinemia 4 (8%) >severe alcohol 2 (4%). The complications were more in ischemic than Nonischemic-CRVO >BRVO - they were macular edema 43 (86%) >neovascularization at iris - 14 (28%) >neovascularization at angle - 10 (20%) >neovascular glaucoma – 4 (8%). Conclusion:RVOs are more common with increasing age, in males & most common risk factor is hypertensive. Most common cause for vision loss is macular edema - ischemic >non-ischemic.